Digitalization of education at the present stage of development of the information society - Hotsalyuk, A.; Chornomordenko, I.; Varekh, N. V.; Dukhanina, N.; Harmatiuk, R.; Варех, Н. В. (Centro Universitário La Salle do Rio de Janeiro, 2023)
The article theoretically substantiates, developed and practically implemented a structural and functional model for the formation of ICT competence of students of a pedagogical university, taking into account interdisciplinary integration; the pedagogical conditions that contribute to the formation of ICT competence of students of a pedagogical university are determined: interdisciplinary integration as the basis for building an interdisciplinary course, the content of which is aimed at the formation of ICT competence; informational, didactic, technological components as a basis for the formation of ICT competence; integration of formal, non-formal and informal education to implement the integrity of the acquired knowledge, skills, experience as the basis for the formation of ICT competence of future teachers; the creation and use of a set of tasks as special means of forming ICT competence, the educational process of a pedagogical university will be built in accordance with the conditions for the digitalization of education and aimed at the formation of students' ICT competence as the basis for the implementation of their future professional activities.
Keywords: Pedagogical strategy; Education; Social innovations; Management